CALCULATION OF HYDRAULIC PRESSURE LOSS IN FILTERING NOZZLES OF MAGNETIC FILTERS - Гаращенко, В. I.; Гаращенко, O. В.; Маланчук, Є. З. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2017)
It was proved that use of magnetic filters with ferromagnetic granular filtering masses for deep purification of technological water of heat power engineering is rational. This allows purification of the technological waters with temperature up to 500ºC and velocity of filtration up to 1000 m/h. During operation of filter the granulated medium creates hydraulic resistance when a stream of water passes through it, which is characterized by a loss of hydraulic pressure and hydraulic resistance coefficient. Based on the large amount of experimental data the improved equation for the coefficient of hydraulic resistance for granular filtering mass, in the form of ball pellets, at values of Reynolds coefficient more than 10 and analytical equations to determine the loss of hydraulic pressure ΔP were obtained. The analytical dependence of ΔP value for filtering materials both in the form of balls and mini parallelepipeds (pellets of crushed steel chips 0Х13-40Х13) were determined. Comparative calculations show that the coefficient of hydraulic resistance of chip mass is three times higher than that of the ball mass. Experiments found that for balls mass with diameter d=3,1mm, porosity ε=0,4, and velocity V=(0,4-2) m/s the value of pressure loss ΔP is 5-6 times higher compared to granules with d=6 mm , ε=0,42, V=(0,3-1,25) m/s, and almost 10 times higher than for the ball granules with d=7,9mm, ε=0,43, V=(0,3-0,8) m/s. After analyzing of the ΔP dependence on V for different diameters a conclusion can be drawn that the increase of ΔP at smaller diameters is explained by "window" geometry (air layer) between granules. The size of "window" with smaller diameters is less, so velocity of the water flow increases and ΔP value increases too.